2008
DOI: 10.15232/s1080-7446(15)30832-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Input Pasture to High-Input Drylot Backgrounding on Performance and Profitability of Beef Calves Through Harvest

Abstract: Over 3 yr, 250 calves (236 kg initial BW; 133 steers and 117 heifers) were used to compare a low-input pasture backgrounding system (PAST) to a highinput drylot system (DLOT) to evaluate performance and profit during the backgrounding (BACKGRD; weaning to 42 to 45 d) and finishing (FINISH; end BACKGRD to slaughter) phases. Calves were randomly assigned to PAST or DLOT treatments during BACKGRD. The DLOT calves were fed a corn-wheat midds-based pellet plus alfalfa hay (0.68 to 1.13 kg/d), and PAST calves were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…A trend was observed (P = 0.06) for the calculated cost of gain between the 3 backgrounding systems in the current study, where CG was lowest (CAN$2.96 ± 0.88/kg) and DL was greatest (CAN$6.32 ± 0.88/kg). These results are in agreement with other studies using extensive grazing systems for backgrounding beef calves (Mathis et al, 2008;Kumar et al, 2012). Kumar et al (2012) reported cost of gain for calves grazing swathed barley was 31% lower than feeding calves in a drylot system.…”
Section: Backgrounding Trialsupporting
confidence: 92%
See 2 more Smart Citations
“…A trend was observed (P = 0.06) for the calculated cost of gain between the 3 backgrounding systems in the current study, where CG was lowest (CAN$2.96 ± 0.88/kg) and DL was greatest (CAN$6.32 ± 0.88/kg). These results are in agreement with other studies using extensive grazing systems for backgrounding beef calves (Mathis et al, 2008;Kumar et al, 2012). Kumar et al (2012) reported cost of gain for calves grazing swathed barley was 31% lower than feeding calves in a drylot system.…”
Section: Backgrounding Trialsupporting
confidence: 92%
“…Therefore, optimal carcass characteristics can be achieved by feeding a diet based on either corn or barley grain, regardless of how calves are backgrounded. These results strongly support the hypothesis that calves can be backgrounded on extensive winter grazing systems without having any negative effect on subsequent feedlot finishing performance, and also agree with previous research reporting that extensive grazing had no negative effect on final steer performance (Vaage et al, 1998;Mathis et al, 2008;Kumar et al, 2012). Beliveau and McKinnon (2008) reported 18% of cattle fed barley-based diets graded AAA, whereas Damiran et al (2014) reported 76% AAA grades.…”
Section: Finishing Trialsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, Bailey et al (2016) reported that calves weaned in a pasture environment for 28 d before feedlot placement had reduced BW gain during the weaning and receiving periods compared with drylot-weaned calves; however, pasture-weaned steers achieved full compensation of BW by harvest with no differences in finishing dry matter intake (DMI), DOF, or carcass characteristics. Similarly, Mathis et al (2008) reported that calves preconditioned on native range weighed less at the end of a 45-d preconditioning period but gained more BW during the first 75 d of finishing than calves preconditioned in a drylot.…”
Section: Introductionmentioning
confidence: 89%
“…Summer grazing supports the cattle industry's competitiveness through low-cost body gains from pasture grazing (Mathis et al, 2008). However, the bites and irritations caused by summer pest flies, such as horn fly (Haematobia irritans irritans), face fly (Musca autumnalis), or stable fly (Stomoxys calcitrans), can have direct negative effects on cattle performance and behavior.…”
Section: Introductionmentioning
confidence: 99%